The Influence of Communication, Work Ethic, Work Motivation, and Organizational Culture on the Work Effectiveness of Java Heritage Hotel Purwokerto Employees - Antika, Rindi Fitri; Widhiandono, Hengky; Rachmawati, Erny; Endratno, Hermin (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study aims to analyze the influence of Communication, Work Ethic, Work Motivation, and Organizational Culture on the effectiveness of the work of Java Heritage Hotel Purwokerto employees and to find out which is more dominant and affects the effectiveness of work. The research sample was 110 Java Heritage Hotel Purwokerto employees using a quota sampling technique. The results showed that communication, work ethic, and motivation significantly affected work effectiveness. Conversely, organizational culture has no effect in the negative direction on work effectiveness. These findings provide valuable insights for hospitality industry leaders. And emphasize to employees the importance of optimizing work effectiveness through communication, work ethic, work motivation. Organizational culture needs to be improved.